The Meaning of Employee Loyalty Among Millennials in the Age of Gig Economy and Side Hustles - Bakhtiar, B.; Molang, Andi (Manunggal Halim Jaya, 2025)
This study explores the evolving meaning of employee loyalty among millennials in the context of the gig economy and the increasing prevalence of side hustles. The primary objective of this research is to examine how millennial employees interpret and experience loyalty to their leading employers while simultaneously engaging in secondary income-generating activities. Employing a qualitative research design grounded in phenomenology, data were collected through in-depth semi-structured interviews and participant journals with 20 millennial professionals from diverse industries, all of whom maintained full-time jobs alongside active side hustles. Thematic analysis revealed four significant loyalty dimensions: relational alignment, conditional commitment, reciprocal trust, and identity integration. Rather than viewing loyalty as absolute or static, participants described it as situational, dynamic, and often negotiated over time based on perceived organizational support, leadership quality, work flexibility, and personal values. Contrary to assumptions that side hustles diminish organizational commitment, findings indicate that when supported and respected, side hustles can enhance employee engagement, innovation, and retention. The study offers theoretical contributions by recontextualizing loyalty through the lens of Social Exchange Theory and Boundaryless Career Theory, while also providing managerial implications for fostering sustainable loyalty in modern, plural workforces. These findings underscore the need for organizations to adopt inclusive and adaptive frameworks that recognize the evolving professional identities of millennial employees in a fluid labor economy.